Due riflessioni sulla poesia (Materiali di Estetica. Terza serie, 2020)
Derrida’s Che cos’è la poesia is a performance of the impossibility of answering the question that sets it off. The poetic cannot comply with philosophical questioning: the text end confessing the arbitrariness of any answer. Following Derrida, if one tries to force poetry to render an account of itself, it enters a prosaic mode and destroys its essence of poetry; poetry therefore cannot communicate what it is to anyone. The image Derrida uses is that of hedgehog trying to cross a road; but a hedgehog is not a hystrix, and some considerations will be developed from this.
Keywords: Derrida; Poetry; Hystrix